Global Navigation Satellite Systems: New Technologies and Applications - Bhatta, Basudeb (CRC Press, 2021)
Global Navigation Satellite Systems (GNSS) and their associated technologies have advanced by leaps and bounds in the nine years since the first edition of this book was published. The concept of survey has changed, especially in the disciplines of geomatics and geoinformatics. This revised and updated second edition provides a thorough understanding of the basic principles and techniques of GNSS, analyzes all four active systems, and explains clearly how each of these systems works. Because of its straightforward treatment of the subject, readers will gain an insight into the techniques, trends, and applications of GNSS and develop knowledge on selecting an appropriate GNSS instrument. Written for students and practitioners in geoinformatics, geomatics engineering, surveying, and remote sensing and GIS, this introductory and practical book includes questions and exercises in each chapter. Key Features: Furnishes detailed information on GPS, GLONASS, Galileo, BeiDou, and other regional and augmented systems Provides practical guidance for surveying, mapping, and navigation with GNSS Sheds light on the latest developments and modern trends of GNSS Includes a detailed glossary of related terms Contains many illustrations that complement the text Exercises for each chapter MCQ solution manual and PPT as online resources